A study of the expression and roles of Bacillus subtilis HtrA-type serine proteases - Noone, David (Trinity College (Dublin, Ireland). Department of Genetics, 2003)
Upon sequencing a region of the Bacillus subtilis genome assigned to the author of this thesis, an open reading frame encoding a homologue of an HtrA-type serine protease, YkdA, was identified. The HtrA serine protease family are common to nearly all eubacteria which can possess one or more paralogues. The HtrA proteases generally respond to stress conditions, typically heat or oxidative insult, and in many pathogens contribute to the virulence of the bacterium. B. subtilis contains three genes encoding members of the HtrA family of serine proteases; ykdA(htrA), yvtA and yycK(yyxA). This work describes an investigation of the expression and roles of the Bacillus subtilis HtrA-type serine proteases.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin